Strategies for strengthening partnerships in circular economy-based plastic waste management - Prabawati, Anindita; Frimawaty, Evi (Applied Environmental Science, 2025)
Background: Asian nations like China, Indonesia, the Philippines, Thailand, and Vietnam account for 60% of the estimated 4.8–12.7 million metric tons of marine plastic trash produced year worldwide. The majority of the marine trash off the north coast of Jakarta is made of plastic, at 59%. Because it offers financial advantages and fosters partner collaboration, the circular economy is a novel strategy for managing plastic trash. Regretfully, there remains a dearth of information regarding the entities engaged in the management of plastic garbage in Central Jakarta. In light of a circular economy, this research attempts to create methods for bolstering collaborations in the management of plastic trash. Methods: In this study, a hybrid strategy using a quantitative approach was employed. The best and most practical type of partnership in Central Jakarta was identified through the use of the Analytical Hierarchy Process (AHP) in this study. Findings: The study's findings indicate that the greatest plan for Central Jakarta is a collaboration with the government since it promotes both well-managed plastic waste management and economic gains. Conclusion: The best partnership model based on AHP analysis is the Government-Private sector partnership. This form of partnership can drive increased economic benefits and improve the performance of plastic waste management. Novelty/Originality of this article: This study integrates a circular economy approach with the Analytic Hierarchy Process (AHP) to determine the most effective partnership model for plastic waste management in Central Jakarta.